0480 Reduction in health care-related costs after initiation of treatment with a prescription digital therapeutic for chronic insomnia: two-year follow up analysis of health care claims data. (25th May 2022) - Forma, Felicia; Knight, Tyler; Thorndike, Francis; Xiong, Ray; Baik, Rebecca; Maricich, Yuri; Velez, Fulton; Malone, Daniel
Abstract: Introduction: The objective of this study was to evaluate the effectiveness of the first FDA-authorized prescription digital therapeutic (PDT) for adults with chronic insomnia that delivers evidence-based treatment (Somryst, previously called SHUTi). FDA considers PDTs to be prescription-only neurobehavioral devices that provide a computerized version of condition-specific behavioral therapy as an adjunct to clinician supervised outpatient treatment. Methods: A pre/post multi-payer analysis of claims data was conducted, comparing two-year pre- and post-index healthcare resource utilization (HCRU) in an all-comer population of patients with self-identified sleep problems across the United States who activated the PDT between February 1, 2012 and December 31, 2018 (Index). HCRU categories assessed were: hospitalizations, treat-and-release emergency department (ED) visits, ambulatory surgical center (ASC) visits, hospital outpatient department (HOPD) visits, office visits, number of sleep medication prescriptions, and associated health care costs. Costs were estimated by multiplying HCRU by published average costs for each medical resource. Results: 252 patients initiating the PDT were analyzed (mean age 54.2 years, 57.5% female). Compared to the pre-index period, post-index events were reduced for ED (-56.2%; P=0.001), hospitalizations (-20.9%; P=0.4), sleep medication use (-8.9%; P=0. 0.377), HOPD (-8.3%; P=0.522), and ASC (-6.7%; P=0.695). Post-index events were slightly increased for office visits (+0.7%; P=0.891). Total estimated two-year cost savings associated with the reduced rates of all services except office visits was $494, 634, or $1, 963 per patient. Conclusion: In a real-world cohort of patients with self-identified sleep problems, treatment with a PDT delivering digital CBT-I was associated with clinically meaningful net reductions in health-related services and associated costs. Support (If Any): This analysis was funded by Pear Therapeutics, Inc.